The relationship between cognitive and physical function among residents of a Czech senior home - Annelies Matthé; Donald N. Roberson; Yael Netz (Palacký University Olomouc, 2015)
Background: The decline in cognition and physical fitness is common in advanced age. Objective: The relationship between cognition and aerobic capacity was compared to the relationship between cognition and balance. Methods: Twenty one females and six male residents of a Czech senior center participated in the study (mean age: 77.5 ± 7.0; range: 62-86 years). The Mini Mental State Examination (MMSE) was used for assessing cognition, the Berg Balance Scale (BBS) for assessing balance, and the 6-Minute Walk Test (6MWT) assessed physical fitness. Based on the MMSE scores, two groups of cognitive functioning were formed - high and low. Results: Participants in the "high MMSE" group reached a significantly higher score on the 6MWT (p = .01) than the "low MMSE" group. Group differences on the BBS were marginally significant (p = .07, d = 0.6). Conclusions: Based on this sample, the level of physical fitness can be explained by cognitive functioning, while that of balance should be further studied in its relationship to cognitive functioning.